The potential role of magnetic resonance spectroscopy in image-guided radiotherapy - Nguyen, Mai L.; Willow, Brooke; Khan, Rihan; Chi, Alexander; Kim, Lyndon; Nour, sherif; Sroka, Thomas; Kerr, Christine; Godinez, Juan; Mills, Melissa; Karlsson, ULF L.; Altdorfer, Gabor; et al. (Frontiers in Oncology, 2014)
Magnetic resonance spectroscopy (MRS) is a non-invasive technique to detect metabolites within the normal and tumoral tissues. The ability of MRS to diagnose areas of high metabolic activity linked to tumor cell proliferation is particularly useful for radiotherapy treatment planning because of better gross tumor volume (GTV) delineation. The GTV may be targeted with higher radiation dose, potentially improving local control without excessive irradiation to the normal adjacent tissues. Prostate cancer and glioblastoma multiforme (GBM) are two tumor models that are associated with a heterogeneous tumor distribution. Preliminary studies suggest that the integration of MRS into radiotherapy planning for these tumors is feasible and safe. Image-guided radiotherapy (IGRT) by virtue of daily tumor imaging and steep dose gradient may allow for tumor dose escalation with the simultaneous integrated boost technique (SIB) and potentially decrease the complications rates in patients with GBM and prostate cancers.